KORELASI ANTARA TINGKAT PENGETAHUAN MENGENAI KODE ETIK JURNALISTIK DENGAN PROFESIONALISME KERJA PERSATUAN WARTAWAN INDONESIA (PWI) KELOMPOK KERJA PEKANBARU - Silmi Hanifa; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Work professionalism is an important component needed by a professionalworker to improve and maintain the quality and quantity of work. In many opinions andtheories, professionalism is supported by several things including professional ethics init. This ethic serves to enable professional workers to know what is appropriate andinappropriate. So that professional workers can work in accordance with social valuesand standard rules of his profession. With so needed knowledge about code of ethics inorder to maintain profesionalism. Therefore, this study aims to determine therelationship between the level of knowledge about the Code of Ethics Journalism WithWorking Professionalism Journalist Indonesia (PWI) Working Group Pekanbaru.The method used in this research is quantitative with correlational approach.The data were collected using questionnaires. The research was conducted inPersatuan Wartawan Indonesia (PWI) Kelompok Kerja Pekanbaru. The sample in thisstudy amounted to 86 respondents. The sampling technique uses accidental sampling.The analysis test used in this research is simple linear regression analysis and toprocess the questionnaire data, done by using program SPSS for Windows version 23.The results obtained from simple linear regression analysis in this study is thelevel of knowledge about the code of ethics journalism has a relationship withprofessionalism work of 45.4%. With a percentage of knowledge level of 67.5%, andprofessionalism of 58%.Keywords: Profesionalism, Knowledge level, Journalist.